Atypical variants of myocardial infarction. Case report of a rare form of acute coronary syndrom with peripheral equivalent of angina - O. A. Khoroshikh (Acta Biomedica Scientifica)
The article presents an actual problem of myocardial infarction in the aspect of atypical variants of its development with a variety of clinical manifestations, prevalence and the most exposed cohorts of patients. A practical difficult-to-differentiate case that demonstrates a rare atypical form of acute coronary syndrome with peripheral equivalent of angina pectoris, with timely diagnosis defined the early onset of adequate treatment and a favorable course of the disease is presented in the article.